Acute B lymphoblastic leukaemia‐propagating cells are present at high frequency in diverse lymphoblast populations. Issue 1 (11th December 2012) - Rehe, Klaus; Wilson, Kerrie; Bomken, Simon; Williamson, Daniel; Irving, Julie; den Boer, Monique L.; Stanulla, Martin; Schrappe, Martin; Hall, Andrew G.; Heidenreich, Olaf; Vormoor, Josef
Abstract: Leukaemia‐propagating cells are more frequent in high‐risk acute B lymphoblastic leukaemia than in many malignancies that follow a hierarchical cancer stem cell model. It is unclear whether this characteristic can be more universally applied to patients from non‐'high‐risk' sub‐groups and across a broad range of cellular immunophenotypes. Here, we demonstrate in a wide range of primary patient samples and patient samples previously passaged through mice that leukaemia‐propagating cells are found in all populations defined by high or low expression of the lymphoid differentiation markers CD10, CD20 or CD34. The frequency of leukaemia‐propagating cells and their engraftment kinetics do not differ between these populations. Transcriptomic analysis of CD34 high and CD34 low blasts establishes their difference and their similarity to comparable normal progenitors at different stages of B‐cell development. However, consistent with the functional similarity of these populations, expression signatures characteristic of leukaemia propagating cells in acute myeloid leukaemia fail to distinguish between the different populations. Together, these findings suggest that there is no stem cell hierarchy in acute B lymphoblastic leukaemia. →See accompanying articlehttp://dx.doi.org/10.1002/emmm.201202207 Abstract : Leukemia propagating cells (LPCs) in B‐ALL are frequent and phenotypically diverse and do not follow a hierarchically organized cancer stem cell model, clarifying a controversial area.